Auditory evoked potential wave VI as an objective indicator of sedation depth in neonates undergoing chloral hydrate sedation: a double-blind randomized controlled study - Zheng, Zong; Yang, Shanpu; Liu, Hongyan; Sheng, Zhimin (Frontiers in Pediatrics, 2025)
BackgroundNeonatal sedation depth monitoring is critical yet depends on the subjective Ramsay scale when used and lacks objective biomarkers. Although auditory evoked potential (AEP) wave VI disappearance is linked to reduced consciousness, its use for neonatal sedation monitoring remains underexplored. We aimed to determine whether wave VI could function as an objective indicator of sedation levels in neonates.MethodsThis prospective, double-blind, randomized trial enrolled 100 neonates requiring hearing screening. Participants were randomly assigned in a 4:1 ratio to either the treatment group (n = 80; 50 mg/kg oral chloral hydrate) or the control group (n = 20; 0.9% saline placebo). The treatment group was further divided into three subgroups according to Ramsay sedation scores, namely, level 4 (n = 22), level 5 (n = 23), and level 6 (n = 35), while the control group was divided into level 3 (n = 5), level 4 (n = 12), and level 5 (n = 3). All neonates received a standardized AEP test performed by an experienced audiologist. Sedation depth was evaluated using the Ramsay scale, and the latency and disappearance rate of wave VI were recorded and correlated with sedation levels. The receiver operating characteristic (ROC) curve was used to evaluate the predictive ability of wave VI latency in deep sedation, analyzing its sensitivity, specificity, and predictive values.ResultsIn the treatment group, wave VI disappearance rates increased in a sedation-dependent manner across the Ramsay Sedation Scale: 0% at level 4, 26% at level 5, and 68.6% at level 6 (p < 0.05). No wave VI disappearance was observed in the control group. ROC analysis demonstrated that wave VI latency predicted deep sedation (Ramsay ≥ 5) with an area under the curve of 0.861 (95% confidence interval: 0.746–0.975). The optimal latency cutoff was 8.465 ms (72.7% sensitivity, 86.2% specificity).ConclusionAEP wave VI latency and disappearance are objective, sensitive, and specific indicators of sedation depth in neonates. With further validation, wave VI has the potential to become a reliable neurophysiological tool for precise sedation monitoring in neonates. Clinical Trial Registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2300068407.